(untitled) (World Bulletin of Education and Learning, 2025)
This article discusses the expression of anthropomorphic metaphors in popular science texts, the study of metaphors by famous linguists, their determination of the place and role of metaphors in language, their great influence on the development of scientific concepts in this regard, as well as the linguistic, sociolinguistic, and cognitive features of metaphors in literary texts, and the effective use of anthropomorphic metaphors in journalistic, and even scientific and official speech styles.